Trichoptera larvae diversity in rivers at various elevation of Gunung Jerai Forest Reserve, Kedah, Malaysia - Suhaila Ab Hamid,; Siti Khatijah Ghazali,; Mohd Shukri Saad, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The abundance and composition of Trichoptera in selected rivers play a significant ecological role in the study of streams, therefore, a study was conducted in three rivers of Gunung Jerai Forest Reserve; Tupah, Batu Hampar and Teroi rivers at altitude range from 200 m to 1214 m above sea level. A total of 2,623 Trichoptera larvae from 11 genera and eight families were collected from the three rivers using a D-frame net. Tupah River recorded the greatest prevalence of Trichoptera (52.3%), followed by Batu Hampar River (42.9%) and Teroi River with the least prevalence (4.8%). Certain genera of Trichoptera such as Cheumatopsyche, Hydropsyche, Macrostemum, Ganonema, Chimarra, Diplectrona and Lepidostoma corresponds to river physical parameters such as altitude, water velocity and water temperature (P<0.05). Results showed Cheumatopsyche from Hydropsychidae had the greatest abundance and diversity associated with high composition in Tupah River which located at lower altitude (200 m above sea level) (r=-0.739, P<0.05). From the number of Trichoptera genera collected in the three rivers at different altitude, clearly show that these caddisflies genera have adapted to live in river with different altitude with stony substrates.